Legal Implications of The Danantara Superholding Model on Public Accountability in State-Owned Bank Asset Management in Indonesia - Pellokila, Catherine Ayunia Zoerien; Sugiharti, Dewi Kania; Affandi, Nurafni Kusumawardhani (Journal of Law, Politic and Humanities, 2025)
State-Owned Enterprises (SOEs) play a crucial role in Indonesia’s economy, yet governance challenges persist, particularly regarding asset management and public accountability. This article critically examines the legal implications of establishing Badan Pengelola Investasi Daya Anagata Nusantara (Danatara), a superholding formed under Law Number 1 of 2025 concerning the Third Amendment to Law Number 19 of 2003, focusing on state-owned banking governance. Using a normative juridical (doctrinal) method supported by comparative studies with Singapore’s Temasek Holdings, this research analyzes the risks of diminished public accountability due to legal separations between Danatara’s investments and state assets. Findings reveal that while the superholding model aims to enhance efficiency, it may weaken constitutional principles concerning state asset control, impair public financial oversight, and obscure transparency and anti-corruption efforts. Moreover, an overemphasis on profitability risks undermining SOEs’ social functions, particularly in financial inclusion and development support. To ensure Danatara fulfills its constitutional mandate, this study recommends strengthening regulatory frameworks, legislative oversight, external audits, and institutional transparency mechanisms.